Flood risk analysis of Vietnam coastal regions - Mai, Cong V. (Hội Thuỷ Lợi, 2020)
In Vietnam, there has been a growing demand for the application of risk analysis, risk based decision making and risk management in various industries and sectors of government. Although the concepts i.e risk analysis and management, have been explored in various industries, there has not been yet any framework/guidance on how risk should be quantified and what would be the acceptable risk/risk criteria. In this paper an overview of concepts for risk management and risk evaluation is given. Risk concepts and methods and applications to establish an acceptable risk level and safety criteria are reviewed. Possible applications to Vietnam of a presented framework for evaluating risk are discussed. It is shown how the framework can be applied to propose an acceptable risk level of flooding at the national scale of Vietnam. The proposed criteria will be tested and applied in the assessment of flood risks in the low-lying coastal regions in Nam Dinh. Safety standards are explored by considering individual and societal acceptable levels of risk, and taking into account the current protected value and socio- economic developments